1998
DOI: 10.1042/bj3300429
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced AP-1 and NF-κB activities and stability of interleukin 8 (IL-8) transcripts are implicated in IL-8 mRNA superinduction in lung epithelial H292 cells

Abstract: Inhibition of protein synthesis may result in superinduction of short-lived transcripts and has been attributed variably to stabilization of transcripts and/or increased gene transcription. Little is known about the kinetics of these processes and relevant transcriptional elements have not been identified. In this study, we describe superinduction of interleukin 8 (IL-8) mRNA, an important inflammatory mediator, in lung epithelial-like H292 cells and identify the underlying molecular mechanisms and their kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
88
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 30 publications
9
88
0
Order By: Relevance
“…4B) and a 2.5-fold increase in the rate of transcript decay (Fig. 4F), in keeping with previous lines of evidence (34,35). The same results were obtained with RNA polymerase II inhibition by DRB (data not shown).…”
Section: Inhibition Of Erk1/2 Signaling Affects Chemokine Expression supporting
confidence: 80%
“…4B) and a 2.5-fold increase in the rate of transcript decay (Fig. 4F), in keeping with previous lines of evidence (34,35). The same results were obtained with RNA polymerase II inhibition by DRB (data not shown).…”
Section: Inhibition Of Erk1/2 Signaling Affects Chemokine Expression supporting
confidence: 80%
“…The IL-11 and IL-6 genes, like the genes for ICAM-1, IL-8 or GM-CSF (Wertheimer et al, 1992;Xing et al, 1993), belong to the group of superinducible genes for which an enhancement of transcript accumulation is induced by protein synthesis inhibitors, albeit via different mechanisms (Maier et al, 1993;Faggioli et al, 1997;Roger et al, 1998a). The IL-8 gene that was superinduced by cycloheximide treatment (10 mg ml 21 ) in lung epithelial H292 cells (Roger et al, 1998b) was not overexpressed in C. trachomatis-infected HeLa cells exposed to 1 mg ml 21 inhibitor, at least at the protein level. Rasmussen et al (1998) showed that, in HeLa cells infected with C. trachomatis serovar L2, the late maximal induction of cytokine resulted from a NF-kB-independent process.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has previously shown that inhibition of MAP kinase activation does not affect NF-B DNA binding activity in response to H. pylori infections (56) and NT (20). Instead, the effect of the MAP kinase pathway in IL-8 gene expression may be mediated through increased transcriptional activity of AP-1, one of three transcriptional factors important for IL-8 gene transcription (22,57,58).…”
Section: Discussionmentioning
confidence: 99%